Simplify and solve the linear equation 3(5z -7) - 2(9z - 11) = 4(8z - 13) - 17

Asked by Aaryan | 1 year ago |  78

##### Solution :-

3(5z - 7) - 2(9z - 11) = 4(8z - 13) - 17

⇒ 15z - 21 - 18z + 22 = 32z - 52 - 17 (Opening the brackets)

⇒ - 3z + 1 = 32z - 69

⇒ - 3z - 32z = - 69 - 1

⇒ - 35z = - 70

⇒ z = $$\frac{70}{35} = 2$$

Answered by Sakshi | 1 year ago

### Related Questions

#### Solve the inequations and graph their solutions on a number line  – 1 < (x / 2) + 1 ≤ 3, x ε l

Solve the inequations and graph their solutions on a number line  – 1 < ($$\dfrac{x}{2}$$) + 1 ≤ 3, x ε l

#### Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

#### Solve (x / 3) + (1 / 4) < (x / 6) + (1 / 2), x ε W. Also represent its solution on the number line.

Solve ($$\dfrac{x}{3}$$) + ($$\dfrac{1}{4}$$) < ($$\dfrac{x}{6}$$) + ($$\dfrac{1}{2}$$), x ε W. Also represent its solution on the number line.

If the replacement set is {-3, -2, -1, 0, 1, 2, 3}, solve the inequation $$\dfrac {(3x – 1) }{2} < 2$$. Represent its solution on the number line.
Solve the inequations ($$\dfrac{3}{2}$$) – ($$\dfrac{x}{2}$$) > – 1, x ε N